Pemanfaatan Barang Bekas Untuk Mendukung Program Go-Green Di MTS Muhammadiyah 10 Wedi - Astuti, Rina; Sriwulan, Riska; Swastihayu, Revivalindra Anandari; Listyanto, Tito Gamas (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2023)
A school go-green program is really needed to support the school's efforts to become a green school and encourage environmentally friendly behavior for students' comfortable learning. The aim of this research is to describe the Go-Green program and the benefits obtained by MTs Muhammadiyah 10 Wedi students and the surrounding community. The method in this research is a qualitative descriptive analysis method. The results of implementing the Go-Green program by using gallons of drinking water to make various kinds of pots at MTs Muhammadiyah 10 Wedi and planting several plants in the pots. Students can use used goods around them. Cohesion and cooperation can also be improved with this program. There are many benefits that can be obtained from the Go-Green program, such as increasing environmental awareness, fostering creativity, and reducing plastic waste.